A Stylistic Study of Aspectual Verbs in Double Negation in Translation of Glorious Qur’an - Haleem Alwhan, Shatha; Abdulkhaliq Majeed, Ibtisam (International Journal of Psychosocial Rehabilitation, 2020)
There is a stylistic problem that cannot be ignored when translating Glorious Qur’an in general, and when translating the negation included in the Glorious Qur’an in particular, as the difference in relation to the stylistic expression of the Glorious Qur’an in general relates to the vast possibilities of the Arabic language. As for the stylistic of double negation in the Arabic language is problematic The Arabic language is shared with the rest of the languages on this point, but in Arabic, this language has a stylistic characteristic, which is the use of double negation to prove meaning or meaning. Is a characteristic of the Glorious Qur’an interpreters cannot understand or deal with it in neutral or even in a language of sound scientific honesty in the transfer of meanings that appear in the context of double negation?